Changes of occlusal plane inclination after orthodontic treatment in different dentoskeletal frames - Li, Jin-le (Prog Orthod, 2014)
BACKGROUND: The inclination of the occlusal plane (OP) is related to facial types and experiences physiological growth-related changes. The aims of this research were to determine if there were any differences in the inclination of OP in subjects with three types of skeletal malocclusion and to investigate the characteristics and differences of functional occlusal plane (FOP) compared to bisected occlusal plane (BOP). METHODS: A sample of 90 Caucasians patients was skeletal-classified into three (n = 30), and pre- and post-treatment cephalograms were digitized. Six linear and 8 angular cephalometric measurements were selected. The changes of OP inclination within each group and the differences among the three groups pre- and post-treatment were compared with paired t test and ANOVA test, respectively. The comparison and correlation between BOP and FOP were analyzed with paired t test and coefficient of correlation, respectively. RESULTS: The BOP angle increased in all of the three groups but only had statistically significant differences in skeletal class II patients in a mean of 1.51° (p < 0.05). The FOP-SN angle showed stability (p > 0.05) in all three groups. The inclination of FOP was closely related to that of BOP (p < 0.001) but revealed discrepancies in each group. CONCLUSIONS: BOP and FOP were statistically significantly steeper in class II subjects compared to the other two groups both before and after treatment. The BOP angle statistically significantly increased by 1.51° in skeletal class II patients. BOP was a more reproducible reference plane compared to FOP during cephalometric tracing process, while FOP showed stability in orthodontically treated patients with all three skeletal patterns. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40510-014-0041-1) contains supplementary material, which is available to authorized users.